The Effectiveness of Spiritual Therapy on Increasing CD4 cell and Quality of Life in AIDS Patients - Afshin Tayyebi; Hasan Ahadi; Saeid Malihzukerini; Amin Rafiepoor; Adis Kraskian Mojembari (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2020)
Aim and Background: AIDS is a medical and social problem that is unfortunately associated with a high prevalence in Iran. This study aimed to investigate the effectiveness of spirituality therapy on increasing CD4 cell and quality of life in AIDS patients.